The Mystery of Time-Space Continuum - Vozbinas, Stanislovas (Problemos, 1990)
The Larmor-Lorentz transformations are considered as a mathematical representation of Doppler’s law. The common group of transformations of the kind with Minkowsky metrics is found. And then the question arises about the real origin and the bounds of employment of relativistic ideas and their representations in the problems of contemporary science and engineering. Leon Brillouin was the first, who has noticed the contradiction hidden in the relativistic interpretation of Doppler’s effect. However, he was unable to solve the contradiction, because in his revision of the relativity problem the natural phenomenon – Doppler’s law – was granted only with the third place, after the energy representation and means, that is, atomic clock. Into the foreground of our analysis we put Doppler’s phenomenon, and as a measure we take Faraday-Maxwell’s representations.